2014
DOI: 10.1111/trf.12672
|View full text |Cite
|
Sign up to set email alerts
|

Perceived barriers among physicians for stopping non–cost‐effective blood‐saving measures in total hip and total knee arthroplasties

Abstract: Background Despite evidence that the blood‐saving measures (BSMs) erythropoietin (EPO) and intra‐ and postoperative blood salvage are not (cost‐)effective in primary elective total hip and knee arthroplasties, they are used frequently in Dutch hospitals. This study aims to assess the impact of barriers associated with the intention of physicians to stop BSMs. Study Design and Methods A survey among 400 orthopedic surgeons and 400 anesthesiologists within the Netherlands was performed. Multivariate logistic reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 37 publications
(98 reference statements)
0
40
1
Order By: Relevance
“…Finally, reflective cognition cannot be used endlessly; an individual's ability to exert self‐control and engage in reflective cognition (eg, problem solving, self‐regulating behaviour, or processing new information) is a finite resource; the more they engage in reflective cognition to make a decision or guide behaviour, the greater the difficulty in exercising reflective cognition for a new task, a condition referred to as ego depletion . This is congruent with research that has highlighted the importance of providing alternatives to clinicians when taking away ineffective practices …”
Section: Introductionmentioning
confidence: 67%
“…Finally, reflective cognition cannot be used endlessly; an individual's ability to exert self‐control and engage in reflective cognition (eg, problem solving, self‐regulating behaviour, or processing new information) is a finite resource; the more they engage in reflective cognition to make a decision or guide behaviour, the greater the difficulty in exercising reflective cognition for a new task, a condition referred to as ego depletion . This is congruent with research that has highlighted the importance of providing alternatives to clinicians when taking away ineffective practices …”
Section: Introductionmentioning
confidence: 67%
“…We use empirical data here from two previously published studies, which are performed at different moments in time: one involving implementation28 29 and one involving de-implementation30 31 among Dutch orthopaedic surgeons. The implementation study aimed to identify factors influencing the implementation of a step-wise strategy of non-surgical therapy for patients with hip and knee osteoarthritis (OA) (including medication and referral guidelines) before undertaking surgical therapy 14.…”
Section: Empirical Datamentioning
confidence: 99%
“…A strength of this study is that it was preceded by a problem analysis study [37, 38, 54]. In this preceding study, we identified the extent of the problem (frequency of use of blood salvage and EPO) and which barriers play a role in this specific situation of low-value care.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy was tailored to address barriers identified in our problem analysis study [38, 40]. The Theoretical Domains Framework (TDF) was used to identify relevant barriers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation